Social Marketing Campaign through a Three-Pile Sorting Game for Bullying Prevention among Elementary School Students - Rohmadtika Dita; Cholifah; Ahmad Meidzal Syauqii (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
Bullying in elementary schools is a serious problem that impacts children's psychological and social development. The community service activity packaged under the title "My School is Safe and Free from Bullying" at SDN Lenteng Agung, Jagakarsa, South Jakarta aims to increase students' understanding and courage in recognizing and preventing bullying behavior. The background of this program is based on the high rate of physical, verbal, relational, and cyber bullying among elementary school students in Indonesia, accompanied by a low level of children's understanding and minimal reporting actions. This campaign was designed with a social marketing approach through material delivery, interactive three pile sorting games, and pre-test and post-test evaluations, so that students can understand the forms and impacts of bullying, how to prevent it, and the importance of reporting. The campaign implementation emphasized the use of simple language and participatory activities to suit the characteristics of elementary school students. A total of 29 students participated in the activity. The results showed an increase in understanding, especially in identifying verbal bullying and cyberbullying. In addition, all students (100%) in the post-test expressed the courage to reprimand the perpetrator and report it to the teacher. These findings indicate that a social campaign based on a participatory approach is effective in increasing anti-bullying literacy while strengthening students' proactive attitudes in creating a safe school environment.